2016
DOI: 10.1007/s11116-016-9712-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequality in mobility and mode choice in Pakistan

Abstract: Using the nationally representative dataset of the 2007 Pakistan Time-Use Survey, this paper examines gender differences in daily trip rate, mode choice, travel duration, and purpose of travel, which are previously unreported because of limited data availability. Wide gender mobility gaps are observed in the country, where women are less likely to travel, are half as mobile as men and may rely heavily on walking. The particular social and cultural context of the country, that renders women as private, secluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 25 publications
0
46
0
2
Order By: Relevance
“…Trip frequency rose between the increasing wealth categories from 'dependent' to 'upper-middle income group'. Adeel (2016) suggested that personal income is positively associated with mobility levels, with those with no income having least mobility. However, Table 4 also shows a slight decrease in mobility between the 'upper-middle-income' and 'high-income' groups.…”
Section: Resultsmentioning
confidence: 99%
“…Trip frequency rose between the increasing wealth categories from 'dependent' to 'upper-middle income group'. Adeel (2016) suggested that personal income is positively associated with mobility levels, with those with no income having least mobility. However, Table 4 also shows a slight decrease in mobility between the 'upper-middle-income' and 'high-income' groups.…”
Section: Resultsmentioning
confidence: 99%
“…al. note in their analysis of Pakistan Time-Use Survey that 80% of all trips outside the house are by males in Pakistan [8]). A qualitative study in a hospital in Rawalpindi by Armaan Rowthor et.…”
Section: Discussionmentioning
confidence: 99%
“…The indifference to this issue is even observed in the developed countries ( Heise et al, 2019 ). Gender inequality in mobility ( Adeel et al, 2017 ) implies that women are less mobile by all means of transportation (because of personal security, home responsibilities) and leads to lower income. This can be offset by remote work practices ( Cama et al, 2016 ; Lörz and Mühleck, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%